Deep-sea urchins of the genus Salenia (Echinoidea - Markov, A. V. (Zoologicheskii Zhurnal, 1988)
Morphology of Salenia hastigera and S. profundi was studied. It is concluded that S. miliaris is a subspecies of S. profundi . Illustrated descriptions of S. p. megalospina subsp.n., S. p. brevispina subsp.n. and S. p. intermedius subsp. n. are presented. Age changes in morphological characters of S. p. miliaris are considered. New data on the range of the studied species are provided to show that S. profundi and S. hastigera occur in the tropical zones of the Pacific, Indian and Atlantic Oceans at the depths of 1,200-4,300 and 370-2,820 m respectively. S. hastigera acuminata MORTENSEN, 1935 and S. profundi occlusa MORTENSEN, 1934 are synonymized with Salenia profundi profundi DUNCAN, 1877.